Modeling Impacts of Nutrient Loading, Warming, and Boundary Exchanges on Hypoxia and Metabolism in a Shallow Estuarine Ecosystem. (21st April 2021) - Testa, Jeremy M.; Basenback, Nicole; Shen, Chunqi; Cole, Kelly; Moore, Amanda; Hodgkins, Casey; Brady, Damian C.
Abstract: We sought to investigate the impacts of nutrient loading, warming, and open‐water boundary exchanges on a shallow estuary through idealized numerical model experiments. We performed these simulations using a stand‐alone implementation of the Regional Ocean Modeling System‐Row‐Column AESOP biogeochemical model in the Chester River estuary, a tributary estuary within the Chesapeake Bay estuarine complex. We found that metabolic rates were elevated in the shallow tributary creeks of the estuary relative to open waters and that rates of gross primary production, respiration, and net ecosystem metabolism were a function of both water temperature and local phytoplankton biomass. Warming 0.75°C and 1.25°C led to reductions in dissolved oxygen concentrations throughout the estuary. Reductions (50%) in dissolved nitrogen and phosphorus loading did not substantially alter hypoxic volumes in this turbid, nutrient‐rich estuary, but warming increased hypoxic volumes by 20%–30%. Alterations of the open‐water boundary that represent improved oxygen concentrations in the adjacent Chesapeake Bay mainstem led to more substantial relief of hypoxia in model simulations than nutrient reductions ( 50% reductions in hypoxia). These simulations reveal the complex interplay of watershed nutrient inputs and horizontal exchange in a small tributary estuary, including the finding that future warming and nutrient reduction effects on Chesapeake Bay hypoxia will be translated to some tributary estuaries like the Chester River.